A 'DYNAMIC EQUIVALENCE TRANSLATION' OF THE BHAGAVAD GITA - Callewaert, W. M. (Journal of Dharma, 1980)
Translators of the Cita (into non-Indian languages) and of the Bible (into Indian languages) are facing very similar problems. They write for a reader who belongs to a culture totally different from the source text, which is religious, ancient and literary. Like the Bible in the West, the Glia. is the most translated book of the Hindu heritage. In English alone, more than 150 different translators have published their translation of the Gird, often with commentary.